Impact of Barney and Friends programme on cognitive development and social skills among early childhood - Noorma Razali (2013)
The purpose of this study was to examine the impact of Barney and Friends programme on cognitive development and social skills among early childhood. A total of 40 children aged between 24 months and 42 months were selected from kindergartens around Indah Permai, Kota Kinabalu, Sabah. This research used experimental design within and between subjects with pre and posttest group design. Bayley Scales of Infants Development (BSID-II) and two CD series of Barney and Friends and Social Skills Checklist were used in this study. Results showed that Barney and Friends programme had significant impact on cognitive development among early childhood. Nevertheless, there was also no significant impact of Barney and Friends programme noticed on social skills among early childhood.